Enhancing Broilers Performance Fed Palm Kernel Expeller (PKE) Feeds Fortified with Supplements (Journal of Biochemistry, Microbiology and Biotechnology, 2020)
Poultry production in Malaysia is heavily dependent on imported feed ingredients. There is a need to utilize local feed ingredients such as palm kernel expeller (PKE) to sustain poultry industry through physical treatments and so that it suitable to be incorporated into the feeds. Hence this study evaluates on the effects of control (0% PKE), untreated PKE (UPKE) , extruded PKE (EPKE), less-shell PKE (LSPKE) and extruded less-shell PKE (ELSPKE) at 10%, 20% and 30% inclusion rates in finisher diets (d 21-42) showed that growth performance of broilers (Cobb 500) fed 10% PKE, 20% LSPKE and ELSPKE, were comparable to control birds. At 30% PKE inclusion, broilers performance was significantly (P
Keywords: palm kernel expeller, physical treatment, extrusion, static cling, growth performance poultry